Beyond training mastering endurance, health, and life - Greenfield, Ben (Las Vegas Victory Belt Publishing, Inc., 2014)
Presents a guide to achieving peak fitness capability by optimizing performance, fat loss, and brain function, covering such aspects of health as nutrition, training, recovery, stress and time management, sleep, and digestion.
Part 1. Fitness -- Part 2. Recovery -- Part 3. Nutrition -- Part 4. Lifestyle -- Part 5. The brain.
Includes index
Keywords: Health; Physical fitness